Dapatkah Altruism Mendorong Konsumen Untuk Melakukan e-WOM? - Rusdiana, Alan; Suparto, L; Istiono, Deni (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
Before the internet appeared, consumers usually talked about various kinds of products and services directly or face to face. This can be considered as word of mouth (WOM) communication. However, along with the internet, there has been a shift related to word of mouth (WOM) to electronic word of mouth (e-WOM). e-WOM is carried out based on experiences related to feelings after using a product or service. Usually consumer feelings will lead to a sense of satisfaction or not after using a product or service. In carrying out e-WOM activities, everyone must have different goals which are in accordance with the motivation of each individual. One thing that is considered important when doing e-WOM is altruism motivation. This study aims to determine the effect of altruism on consumer behavior to share eWOM. This type of research is classified as associative research. The population in this study are all students of the Faculty of Economics and Business, Majalengka University who use Tokopedia e-commerce. The sample in this study amounted to 100 people who were taken using accidental sampling technique. The data analysis method used multiple linear regression analysis which first tested the research instrument and the classical assumption test, then tested the hypothesis of the SPSS 21 program. Based on the hypothesis test, it was found that altruism motivation has a positive and significant effect on e-WOM behavior. That is, the higher the altruism possessed by consumers, the higher the willingness of consumers to carry out e-WOM on Tokopedia e-commerce.